2007
DOI: 10.1089/acm.2006.6401
|View full text |Cite
|
Sign up to set email alerts
|

Side-Effects of Massage Therapy: A Cross-Sectional Study of 100 Clients

Abstract: This the first known study to define the rate of side-effects after massage therapy treatment. These data are important for risk-benefit analyses of massage care. Larger studies are needed to verify these data and to assess effects of different massage types and durations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 7 publications
0
32
1
1
Order By: Relevance
“…In a study designed to assess the side effects of massage therapy, 10% of massage clients experienced minor musculoskeletal discomfort after a massage session. 45 Future studies are needed to assess the effects of applying pressure to the back versus other body parts after cardiac surgery. Furthermore, we assessed physiologic variables immediately after usual care or after a massage session.…”
Section: Discussionmentioning
confidence: 99%
“…In a study designed to assess the side effects of massage therapy, 10% of massage clients experienced minor musculoskeletal discomfort after a massage session. 45 Future studies are needed to assess the effects of applying pressure to the back versus other body parts after cardiac surgery. Furthermore, we assessed physiologic variables immediately after usual care or after a massage session.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that in addition to relieving bodily pain, the immediate effects of inducing relaxation and improving mood may be common reasons for consulting a massage therapist (Cambron et al 2007;Cherkin et al 2002). However a previous small study, conducted in the US, found that elderly (mean age = 67.4 years) chronic pain patients who have used massage in the previous 12 months showed significantly higher quality of life scores (including emotional health) compared to non-users (Munk et al 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…7 Massage is a systematic form of touch that manipulates soft tissues of the body to promote comfort and healing. 9 Massage therapy might have minor adverse effects, 10 such as bruising, headache, and fatigue, 10,11 but rarely serious adverse effects (i.e., cerebrovascular accidents or hematomas). The majority of adverse effects were associated with exotic types of manual massage or massage delivered by laypersons.…”
Section: Introductionmentioning
confidence: 99%